Cloud Computing-Overview (International Journal of Engineering and Computer Science, 2014)
Cloud communications and cloud-based computing are seemingly on a steep growth curve. Cloud computing is an increasingly popular paradigm for accessing computing resources. In practice, cloud service providers tend to offer services that can be grouped into three categories: software as a service (SAAS), platform as a service (PAAS), and infrastructure as a service (IAAS). Cloud computing, with the revolutionary promise of computing as a utility, has the great potential to transform how IT services are delivered and managed. Yet, despite its great promise, even the most seasoned professionals know little about cloud computing or how to define it.